Telaah Pemikiran Muhaddithin dan Usuliyyin terhadap Hadith al-Jinayah sebagai Hujjah dalam Memutuskan Hukum Pidana Islam - Al Hadi, Abu Azam (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
Al-hadith positions as the foundation of Islamic law does not cover all kinds and types of al-hadith, even though the Qur'an has shown its validity. The Ulama attitude toward al hadits is influenced by several factors. Some take all hadith as the basis for Islamic law (including determining the provisions of Islamic jinayah/criminal punishments), and some do not. Some ulama are critical of al-hadith as a rationale of the Islamic shari'ah argument, some are merely positive, and some reject a part of al-hadith as a basis. According to Ulama Muhaddistsun and Ushuliyyun, al-hadith al-maqbullah must be based on various criteria. It must be narrated by a narrator who is fair and dabit, there is no 'illah al-qadihah, and the narration is not experiencing shudud. Muhaddithun took the attitude to accept all hadith, whether authentic, hasan or da'if, all to be practised. On the other hand, the ushuliyyun take the basis of istinbat only on the proposition of hadith shahih or hasan as ma'mul bih. This attitude extends to al-hadith ghayr al-mutawatirah, which provides benefits for yaqin. According to them, if the hadith is ghayru ma'mul bih, it is rejected.